2016
DOI: 10.1111/scs.12284
|View full text |Cite
|
Sign up to set email alerts
|

Differences in predictors of 5‐year survival over a 10‐year period in two cohorts of elderly nursing home residents in Sweden

Abstract: The present results indicate a trend that individuals are older and frailer when admitted to NH and that survival time after admission has been shortened. Hence, the need of daily support and care has increased, irrespective of housing. Also, predictors of survival, possible to influence, have changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 15 publications
1
36
1
8
Order By: Relevance
“…7 The median length of survival was 2.70-2.99 years in Norway. In previous 5-year studies in which the survival time was stated, the mean length of survival was 4.97 years in Hong Kong 4 and 2.58-3.17 years in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The median length of survival was 2.70-2.99 years in Norway. In previous 5-year studies in which the survival time was stated, the mean length of survival was 4.97 years in Hong Kong 4 and 2.58-3.17 years in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…7 The median length of survival was 2.70-2.99 years in Norway. [2][3][4][5]7 Among the significant predictors, only sex, nutritional status, cognitive status, and depressive symptoms, but not the number of diseases, had been identified in previous studies. By comparison, it was 80.7 years in another study carried out in Hong Kong, 4 81.6-86.7 years in Sweden 7 and 85.3-85.7 years in Norway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, they are akin to what is referred to in the US as assisted-living residences because they are guided by ordinary tenancy agreements and have the ambition to cater to both social and medical care (Nord 2011(Nord , 2013. For residents, the nursing home is often their last home in life (Sund Levander et al 2016). However, because living in a nursing home requires individual needs assessment, Swedish government reports also concluded that older people were at risk of being unwillingly separated from their spouse or partner in the transition to residential care (Ministry of Health and Social Affairs 2011).…”
Section: The Cohabitation Guaranteementioning
confidence: 99%
“…Eligibility to move to a nursing home is established by a municipal care manager who judges if the older person's needs can no longer be met in other ways through the system of home care. Accordingly, nursing home residents are often very old, frail, and have multiple health conditions (Sund Levander et al 2016).…”
Section: The Cohabitation Guaranteementioning
confidence: 99%